Diverse Virus and Host-Dependent Mechanisms Influence the Systemic and Intrahepatic Immune Responses in the Woodchuck Model of Hepatitis B - Michalak, Tomasz I. (Frontiers in Immunology, 2020)
Woodchuck infected with woodchuck hepatitis virus (WHV) represents the closest pathogenic model of hepatitis B and associated hepatocellular carcinoma (HCC). This naturally occurring system also is highly valuable for development and preclinical evaluation of new anti-HBV agents and immunotherapies against chronic hepatitis (CH) and HCC. Studies in this model uncovered a number of molecular and immunological processes which play or likely play a role in the immunopathogenesis of liver disease and in modulation of the systemic and intrahepatic innate and adaptive immune responses during hepadnaviral infection. Among them, inhibition of the class I major histocompatibility complex presentation on chronically infected hepatocytes and a role of virus envelope proteins in this process, as well as augmented hepatocyte cytotoxicity mediated by constitutively expressed components of CD95 (Fas) ligand- and perforin-dependent pathways, capable of eliminating cells brought to contact with hepatocyte surface, including activated T lymphocytes, were uncovered. Other findings pointed to a role of autoimmune response against hepatocyte asialoglycoprotein receptor in augmenting severity of liver damage in experimental CH. It was also documented that WHV in the first few hours activates intrahepatic innate immunity that transiently decreases hepatic virus load. However, this activation is not translated in a timely manner to induction of virus-specific T cell response which appears to be hindered by defective activation of antigen presenting cells and a delay in presenting viral epitopes to T cells. The early WHV infection also induces generalized polyclonal activation of T cells that precedes emergence of virus-specific T lymphocyte reactivity. The combination of these mechanisms hamper initial recognition of virus permitting its dissemination in the very early, asymptomatic stages of infection before adaptive cellular response became effective. This review will highlight a range of diverse mechanisms uncovered in the woodchuck model which influence effectiveness of the anti-viral systemic and intrahepatic immune responses, and modify liver disease outcomes. Further exploration of these and other mechanisms either already discovered and yet unknown and their interactions should bring more complete understanding of HBV pathogenesis and help to identify new targets for therapeutic interventions. The woodchuck model is uniquely positioned to further contribute to these advances.